PENGARUH CaCl2.2H2O DAN WAKTU INKUBASI TERHADAP PRODUKSI INULINASE OLEH Pichia manshurica DUCC Y-015 DALAM SUBSTRAT TEPUNG UMBI DAHLIA - Dahniar Saraswati; W Wijanarka; MG Isworo Rukmi (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Fructose production from inulin by inulinase only need one reaction enzimatic step and produce 95% fructose. Inulin obtained from dahlia tuber and inulinase produced by Pichia manshurica DUCC Y-015. Inulinase production (E.C. 3.2.1.7.) can be influenced by metal salt suplementation, such as CaCl2.2H2O. The purpose of this research were to known the influence of CaCl2.2H2O and incubation time to inulinase production by P. manshurica DUCC Y-015 on Dahlia Tuber Substrate. The design that use in this research were Randomized Factorial Block Design ( RAFBD ). Factor I (CO, C1, C2, C3) as the concentration of CaCl2.2H2O (0 mM, 0.25 mM, 0.50 mM, 1.00 mM) and Factor II ( T12, T18, dan T24 ) as incubation time ( 6, 12, 18 hour), the repetition were 3 times. The result analyze by ANOVA (Analysis of Variance) and continued by LSD test. The result of this research indicate that CaCl2.2H2O and incubation time were not significantly influence to inulinase production. The highest inulinase production by Pichia manshurica DUCC Y-015 indicate by C2T12 treatment which use 0.50 mM CaCl2.2H2O and 12 hour incubation time, the enzyme activity is 0.60 IU/mLKey Words : CaCl2.2H2O, Dahlia tuber, Incubation time, Inulin, Inulinase, Pichia manshurica DUCC Y-015.